Changes in volatile composition during fruit development and ripening of `Alphonso' mango - Pandit, Sagar S.; Kulkarni, Ram S.; Chidley, Hemangi G.; Giri, Ashok P.; Pujari, Keshav H.; Koellner, Tobias G.; Degenhardt, Joerg; Gershenzon, Jonathan; Gupta, Vidya S. (Journal of the Science of Food and Agriculture, 2009)
BACKGROUND: Volatile blends of five developing and five ripening stages of mango (Mangifera indica L. cv. Alphonso) were investigated along with those of flowers and leaves. Raw and ripe fruits of cv. Sabia were also used for comparison. RESULTS: A total of 55 volatiles belonging to various chemical classes such as aldehydes, alcohols, mono- and sesquiterpene hydrocarbons, lactones and furanones were identified. In all Alphonso tissues monoterpenes quantitatively dominated, with 57-99% contribution; in particular, (Z)-ocimene was found in the highest amount. Ripeness was characterized by the de novo appearance of lactones and furanones in the blend of monoterpenes. Sabja was distinguished by the abundance of monoterpene hydrocarbons in the raw fruit, and that of sesquiterpene hydrocarbons and their derivatives in the ripe stage. CONCLUSION: Various stages of the Alphonso fruit during transition from flower to ripe fruit are characterized by unique volatile signatures that are distinguished from each other by the qualitative and quantitative appearance of different volatile compounds. Thus volatiles can be highly informative markers while studying the development and ripening of mango. (C) 2009 Society of Chemical Industry
Keywords: Deogad; Gas chromatography; Mangifera indica; mango products; ripening indicator; Sabja

Cultivar relationships in mango based on fruit volatile profiles - Pandit, Sagar S.; Chidley, Hemangi G.; Kulkarni, Ram S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Food Chemistry, 2009)
Aroma volatiles of mango (Mangifera indica L.) determine consumer acceptability and influence selection, whilst breeding. To assess their variety, composition and possible impact on cultivar relationships, volatile blends of 22 Indian and five non-Indian cultivars were investigated using solvent extraction and gas chromatography. Totally 84 volatiles belonging to various chemical classes were detected. Based on the Cumulative Occurrence of members of these classes, cultivars were grouped as monoterpene or sesquiterpene dominant. a-Pinene, beta-myrcene and beta-caryophyllene were found in all 27 cultivars. For ordination, common compounds with high (relative) concentration provided quantitative characters, whereas the rare and lesser ones provided qualitative (binary) characters; non-Indian cultivars separated from Indian ones but displayed close relations within their groups. In conclusion, mango flavour is dominated qualitatively as well as quantitatively by terpene hydrocarbons; ancient selection of mango cultivars is hinted to be driven by different aroma characters in different parts of the world. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Flavour; GC-MS; Mangifera indica; Multivariate analysis; Ordination

Geographic variation in the flavour volatiles of alphonso mango - Kulkarni, Ram S.; Chidley, Hemangi G.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Food Chemistry, 2012)
Alphonso, one of the most popular cultivars of mango in India is known to exhibit geographic variation in the flavour of ripe fruits. To get chemical insight into this difference, volatiles were studied in the ripening fruits of Alphonso mangoes from three cultivation locations in India. Ripe fruits from Deogad had lower content of mono- and sesquiterpenes and higher content of lactones and furanones as compared to the fruits from Dapoli: whereas fruits from Vengurle had average quantities of these chemicals in comparison with Deogad and Dapoli fruits. This variation was clearly reflected as separate clustering of the localities in the Principal Component Analysis. The localities were indistinguishable from each other in terms of raw fruit volatiles. This study exemplifies a case of phenotypic plasticity; since the plants chosen were clonally propagated, such geographic variation in the volatiles can be attributed to varied abiotic conditions at these three localities. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Mango; Phenotypic plasticity; Ripening; Volatiles

Characterization of three novel isoprenyl diphosphate synthases from the terpenoid rich mango fruit - Kulkarni, Ram; Pandit, Sagar; Chidley, Hemangi G.; Nagel, Raimund; Schmidt, Axel; Gershenzon, Jonathan; Pujari, Keshav; Giri, Ashok P.; Gupta, Vidya (Plant Physiology and Biochemistry, 2013)
Mango (cv. Alphonso) is popular due to its highly attractive, terpenoid-rich flavor. Although Alphonso is clonally propagated, its fruit-flavor composition varies when plants are grown in different geo-climatic zones. Isoprenyl diphosphate synthases catalyze important branch-point reactions in terpenoid biosynthesis, providing precursors for common terpenoids such as volatile terpenes, sterols and carotenoids. Two geranyl diphosphate synthases and a farnesyl diphosphate synthase were isolated from Alphonso fruits, cloned for recombinant expression and found to produce the respective products. Although, one of the geranyl diphosphate synthases showed high sequence similarity to the geranylgeranyl diphosphate synthases, it did not exhibit geranylgeranyl diphosphate synthesizing activity. When modeled, this geranyl diphosphate synthase and farnesyl diphosphate synthase structures were found to be homologous with the reference structures, having all the catalytic side chains appropriately oriented. The optimum temperature for both the geranyl diphosphate synthases was 40 degrees C and that for farnesyl diphosphate synthase was 25 degrees C. This finding correlated well with the dominance of monoterpenes in comparison to sesquiterpenes in the fruits of Alphonso mango in which the mesocarp temperature is higher during ripening than development. The absence of activity of these enzymes with the divalent metal ion other than Mg2+ indicated their adaptation to the Mg2+ rich mesocarp. The typical expression pattern of these genes through the ripening stages of fruits from different cultivation localities depicting the highest transcript levels of these genes in the stage preceding the maximum terpene accumulation indicated the involvement of these genes in the biosynthesis of volatile terpenes. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Alphonso; Flavor variation; Fruit; Isoprenyl diphosphate synthase; Mangifera indica; Terpene volatiles

Oxidoreductase from `Alphonso' mango catalyzing biosynthesis of furaneol and reduction of reactive carbonyls - Kulkarni, Ram; Chidley, Hemangi G.; Deshpande, Ashish; Schmidt, Axel; Pujari, Keshav; Giri, Ashok P.; Gershenzon, Jonathan; Gupta, Vidya (SpringerPlus, 2013)
Two furanones, furaneol (4-hydroxy-2,5-dimethyl-3(2H)-furanone) and mesifuran (2,5-dimethyl-4-methoxy-3(2H)-furanone), are important constituents of flavor of the Alphonso cultivar of mango (Mangifera indica). To get insights into the biosynthesis of these furanones, we isolated an enone oxidoreductase gene from the Alphonso mango. It has high sequence similarity to an alkenal/one oxidoreductase from cucumber (79% identity) and enone oxidoreductases from tomato (73% identity) and strawberry (72% identity). The complete open reading frame was expressed in E. coli and the (his) 6-tagged recombinant protein was purified by affinity chromatography. The purified protein assayed with NADH as a reducing agent converted D-fructose-1,6-diphosphate into furaneol, the immediate precursor of mesifuran. The enzyme was also able to convert two highly reactive carbonyls, 3-buten-2-one and 1-penten-3-one, produced by lipid peroxidation in plants, into their saturated derivatives. Expression profiling in various ripening stages of Alphonso fruits depicted an expression maxima at 10 days after harvest stage, shortly before the appearance of the maximum amount of furanones (completely ripe stage, 15 days after harvest). Although no furanones were detected at the 0 day after harvest stage, significant expression of this gene was detected in the fruits at this stage. Overall, the results suggest that this oxidoreductase plays important roles in Alphonso mango fruits.
Keywords: Detoxification; Enone oxidoreductase; Flavor; Mangifera indica; Ripening

Spatial and temporal changes in the volatile profile of alphonso mango upon exogenous ethylene treatment - Chidley, Hemangi G.; Kulkarni, Ram S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Food Chemistry, 2013)
Alphonso is a highly favoured and exported mango cultivar among the vast mango germplasm of India. Being a climacteric fruit, ethylene plays an important role in ripening of mango. For deeper understanding of effect of pre-climacteric ethylene treatment on volatile profiles of Alphonso mango, 26 volatiles were tracked through six ripening stages of pulp and skin of ethylene-treated and control Alphonso fruits. The study revealed accelerated ripening in terms of early appearance of ripening-specific compounds, lactones and mesifuran, upon ethylene treatment. While the level of lactones remained unaffected, the mesifuran level vastly increased upon ethylene treatment. Skin showed high terpene content while pulp had higher amount of lactones compared to skin. This work points towards involvement of ethylene as a natural hormone in the biosynthesis of lactones and furanones in naturally ripened fruits; whereas, an increase in the terpene level during ripening appears to be independent of ethylene. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Ethylene; Flavour; Mango; Pre-climacteric; Ripening; Volatiles

Molecular cloning and characterization of O-methyltransferase from mango fruit (mangifera indica cv. alphonso) - Chidley, Hemangi G.; Oak, Pranjali S.; Deshpande, Ashish B.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Molecular Biotechnology, 2016)
Flavour of ripe Alphonso mango is invariably dominated by the de novo appearance of lactones and furanones during ripening. Of these, furanones comprising furaneol (4-hydroxy-2,5-dimethyl-3(2H)-furanone) and mesifuran (2,5-dimethyl-4-methoxy-3(2H)-furanone) are of particular importance due to their sweet, fruity caramel-like flavour characters and low odour detection thresholds. We isolated a 1056 bp complete open reading frame of a cDNA encoding S-adenosyl-l-methionine-dependent O-methyltransferase from Alphonso mango. The recombinantly expressed enzyme, MiOMTS showed substrate specificity towards furaneol and protocatechuic aldehyde synthesizing mesifuran and vanillin, respectively, in an in vitro assay reaction. A semi-quantitative PCR analysis showed fruit-specific expression of MiOMTS transcripts. Quantitative real-time PCR displayed ripening-related expression pattern of MiOMTS in both pulp and skin of Alphonso mango. Also, early and significantly enhanced accumulation of its transcripts was detected in pulp and skin of ethylene-treated fruits. Ripening-related and fruit-specific expression profile of MiOMTS and substrate specificity towards furaneol is a suggestive of its involvement in the synthesis of mesifuran in Alphonso mango. Moreover, a significant trigger in the expression of MiOMTS transcripts in ethylene-treated fruits point towards the transcriptional regulation of mesifuran biosynthesis by ethylene.
Keywords: Ethylene; expression; Flavour; Mango; Mesifuran; Ripening

Effect of postharvest ethylene treatment on sugar content, glycosidase activity and its gene expression in mango fruit - Chidley, Hemangi G.; Deshpande, Ashish B.; Oak, Pranjali S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Journal of the Science of Food and Agriculture, 2017)
BACKGROUND: Ripening-associated softening is one of the important attributes that largely determines the shelf-life of mango (Mangifera indica Linn.) fruits. To reveal the effect of pre-climacteric ethylene treatment on ripening-related softening of Alphonso mango, ethylene treatment was given to mature, raw Alphonso fruits. Changes in the pool of reducing and non-reducing sugars, enzymatic activity of three glycosidases: ss-D-galactosidase, alpha-D-mannosidase and ss-D-glucosidase and their relative transcript abundance were analysed for control and ethylene treated fruits during ripening. RESULTS: Early activity of all the three glycosidases and accelerated accumulation of reducing and non-reducing sugars on ethylene treatment was evident. ss-D-Galactosidase showed the highest activity among three glycosidases in control fruits and marked increase in activity upon ethylene treatment. This was confirmed by the histochemical assay of its activity in control and ethylene treated ripe fruits. Relative transcript abundance revealed high transcript levels of ss-D-galactosidase in control fruits. Ethylene-treated fruits showed early and remarkable increase in the ss-D-galactosidase transcriptswhile alpha-D-mannosidase transcript variants displayed early accumulation. CONCLUSION: Thefindings suggest reduction in the shelf-life of Alphonso mango upon pre-climacteric ethylene treatment, a significant role of ss-D-galactosidase and alpha-D-mannosidase in the ripening related softening of Alphonso fruits and transcriptional regulation of their expression by ethylene. (C) 2016 Society of Chemical Industry

Isolation and characterization of 9-lipoxygenase and epoxide hydrolase 2 genes: insight into lactone biosynthesis in mango fruit (Mangifera indica L.) - Deshpande, Ashish B.; Chidley, Hemangi G.; Oak, Pranjali S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Phytochemistry, 2017)
Uniqueness and diversity of mango flavour across various cultivars are well known. Among various flavour metabolites lactones form an important class of aroma volatiles in certain mango varieties due to their ripening specific appearance and lower odour detection threshold. In spite of their biological and biochemical importance, lactone biosynthetic pathway in plants remains elusive. Present study encompasses quantitative real-time analysis of 9-lipoxygenase (Mi9LOX), epoxide hydrolase 2 (MiEH2), peroxygenase, hydroperoxide lyase and acyl-CoA-oxidase genes during various developmental and ripening stages in fruit of Alphonso, Paid and Kent cultivars with high, low and no lactone content and explains their variable lactone content. Study also covers isolation, recombinant protein characterization and transient over-expression of Mi9LOX and MiEH2 genes in mango fruits. Recombinant Mi9LOX utilized linoleic and linolenic acids, while MiEH2 utilized aromatic and fatty acid epoxides as their respective substrates depicting their role in fatty acid metabolism. Significant increase in concentration of delta-valerolactone and gamma-decalactone upon Mi9LOX over-expression and that of delta-valerolactone, gamma-hexalactone and delta-hexalactone upon MiEH2 over-expression further suggested probable involvement of these genes in lactone biosynthesis in mango. (C) 2017 Elsevier Ltd. All rights reserved.

Transcriptional transitions in alphonso mango (Mangifera indica L.) during fruit development and ripening explain its distinct aroma and shelf life characteristics - Deshpande, Ashish B.; Anamika, Krishanpal; Jha, Vineet; Chidley, Hemangi G.; Oak, Pranjali S.; Kadoo, Narendra Y.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Scientific Reports, 2017)
Alphonso is known as the "King of mangos" due to its unique flavor, attractive color, low fiber pulp and long shelf life. We analyzed the transcriptome of Alphonso mango through Illumina sequencing from seven stages of fruit development and ripening as well as flower. Total transcriptome data from these stages ranged between 65 and 143 Mb. Importantly, 20,755 unique transcripts were annotated and 4,611 were assigned enzyme commission numbers, which encoded 142 biological pathways. These included ethylene and flavor related secondary metabolite biosynthesis pathways, as well as those involved in metabolism of starch, sucrose, amino acids and fatty acids. Differential regulation ( p-value <= 0.05) of thousands of transcripts was evident in various stages of fruit development and ripening. Novel transcripts for biosynthesis of mono-terpenes, sesqui-terpenes, di-terpenes, lactones and furanones involved in flavor formation were identified. Large number of transcripts encoding cell wall modifying enzymes was found to be steady in their expression, while few were differentially regulated through these stages. Novel 79 transcripts of inhibitors of cell wall modifying enzymes were simultaneously detected throughout Alphonso fruit development and ripening, suggesting controlled activity of these enzymes involved in fruit softening.